Leland Stanford, Mr. Gay San Jose, marching - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Leland Stanford III, Mr. Gay San Jose, (second from right) marching with other participants in the National March on Washington for Lesbian and Gay Rights. The lettering on his shirt reads, "Lee Stanford, Mr. Gay S.J.".